Ophthalmic emergency manual - Bdour, Muawyah D Al; Ameerh, Mohammed A. Abu (Jaypee Brothers Medical Publishers, 2014)
Concise guide to the diagnosis, management and referral of ocular emergencies. Divided into eight sections, the book examines disorders in different parts of the eye. Includes comprehensive appendices section.